Integrated Nutrient Management on Growth and Productivity of Rapeseed-mustard Cultivars - Saha, P. K.; Malik, G. C.; Bhattacharyya, P.; Banerjee, M. (International Journal of Bio-resource and Stress Management, 2015)
To find out the efficacy of different integrated nutrient management a field experiment was conducted at Pulses and Oilseeds Research Station, Berhampore, W.B, during Rabi season of 2009-10 and 2010-11 on Rapeseed-Mustard. The experiment was laid out in split plot design and replicated thrice with three varieties viz., V1, Binoy (B -9); V2, Sarama; V3, Kalyan(WBBN-1) in main plots and five fertility management {F1= 100-50-50-30 N-P2O5-K2O, S kg ha-1 (recommended), F2=RD+5 t FYM ha-1, F3=RD+5 t FYM+Azotobacter, F4=RD+5 t FYM+PSB., F5=RD+5 t FYM+PSB.+Azotobacter} as sub-plot treatments. The highest plant height (cm), number of primary branches plant-1 and dry matter accumulation (g) were achieved in the crops receiving a combinations of fertility treatment with the recommended dose of chemical fertilizers along with FYM, Azotobacter and PSB during both the years. Significant increase in yield was found in Sarama variety followed by the variety Binoy and Kalyan. The application of RD+2 t FYM+PSB+Azotobacter resulted significant increase in Seed yield, biological yield and oil percentage in all Rapeseed-Mustard varieties. The highest net return of ` 22106.56 and ` 23262.11 ha-1 respectively during the two years of the experimentation were recorded from the rapeseed-mustard crop raised with the recommended dose of chemical fertilizers, FYM, Azotobacter and PSB together. The benefit cost ratio also indicated that the treatment R.D+2 t FYM+PSB+Azotobacter was more remunerative.